Visible-Light Stiffness Patterning of GelMA Hydrogels Towards In Vitro Scar Tissue Models - Chalard, Anaïs E.; Dixon, Alexander W.; Taberner, Andrew J.; Malmström, Jenny (Frontiers in Cell and Developmental Biology, 2022)
Variations in mechanical properties of the extracellular matrix occurs in various processes, such as tissue fibrosis. The impact of changes in tissue stiffness on cell behaviour are studied in vitro using various types of biomaterials and methods. Stiffness patterning of hydrogel scaffolds, through the use of stiffness gradients for instance, allows the modelling and studying of cellular responses to fibrotic mechanisms. Gelatine methacryloyl (GelMA) has been used extensively in tissue engineering for its inherent biocompatibility and the ability to precisely tune its mechanical properties. Visible light is now increasingly employed for crosslinking GelMA hydrogels as it enables improved cell survival when performing cell encapsulation. We report here, the photopatterning of mechanical properties of GelMA hydrogels with visible light and eosin Y as the photoinitiator using physical photomasks and projection with a digital micromirror device. Using both methods, binary hydrogels with areas of different stiffnesses and hydrogels with stiffness gradients were fabricated. Their mechanical properties were characterised using force indentation with atomic force microscopy, which showed the efficiency of both methods to spatially pattern the elastic modulus of GelMA according to the photomask or the projected pattern. Crosslinking through projection was also used to build constructs with complex shapes. Overall, this work shows the feasibility of patterning the stiffness of GelMA scaffolds, in the range from healthy to pathological stiffness, with visible light. Consequently, this method could be used to build in vitro models of healthy and fibrotic tissue and study the cellular behaviours involved at the interface between the two.